(untitled) (Società e diritti, 2022)
The article analyzes the socio-economic thought of Giuseppe Toniolo (1845 - 1918), starting with the book recently written by Mons. Domencio Sorrentino, Bishop of Assisi-Nocera Umbra-Gualdo Tadino and Foligno, concerning “Economia umana. La lezione e la profezia di Giuseppe Toniolo: una rilettura sistematica”, Vita e Pensiero, Milano, 2021. Giuseppe Toniolo, economist and sociologist, going against the mainstream of his time coinceived economy as a social science because it had been humanized by his contamination with catholic spirituality and social ethics. The article is titled “Giuseppe Toniolo Master and Prophet” because it highlights the example of life and the courageous lesson of this scholar member of the ethical-legal school of economy and the legacy of his teaching still valid today..